2023
DOI: 10.1002/smll.202370065
|View full text |Cite
|
Sign up to set email alerts
|

Cascade Delivery to Golgi Apparatus and On‐Site Formation of Subcellular Drug Reservoir for Cancer Metastasis Suppression (Small 11/2023)

Abstract: Cancer Metastasis Suppression In article number 2204747, Yuan Huang and co‐workers develop a strategy that enhances the targetability and retention of nano‐drug in Golgi apparatus (GA) for cancer metastasis suppression. Hybrid cell membrane‐coated nanoparticles cascade to delivering cargo into GA, and in return, loaded‐Monensin, an exocytosis inhibitor, blocks nano‐drug exocytosis like steel net. With GA retention of nano‐drug and GA dysfunction, this strategy suppresses metastasis initialization via multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…So far, scientists have developed numerous surface and interface engineering strategies to achieve high selectivity and sensitivity in biological and chemical detection, aiming for accurate healthcare or early diagnosis. [13,26,42,45,[68][69][70] Different surface/interface modulation methods correspondingly vary depending on the analytes and sensing mechanism.…”
Section: General Strategies Of High-performance Sensors For Healthcar...mentioning
confidence: 99%
See 1 more Smart Citation
“…So far, scientists have developed numerous surface and interface engineering strategies to achieve high selectivity and sensitivity in biological and chemical detection, aiming for accurate healthcare or early diagnosis. [13,26,42,45,[68][69][70] Different surface/interface modulation methods correspondingly vary depending on the analytes and sensing mechanism.…”
Section: General Strategies Of High-performance Sensors For Healthcar...mentioning
confidence: 99%
“…Due to the operation of device in the electrolyte and ionic/electron mixed signal amplification capability, OECT has received much more attention on biosensing field in recent years. [27,42,67,68]…”
Section: General Introduction Of Organic Transistors and Strategiesmentioning
confidence: 99%
“…[15] At present, Ru/Ir-based and Pt-based noble metal catalysts show excellent OER and HER electrocatalytic properties, but due to the scarcity and high production cost of such metals, they cannot be widely applied in commercial devices. [16][17][18] Thus, the exploitation of inexpensive and efficient non-noble metal electrocatalysts has become a research priority. [19][20][21] Transition metal elements Fe, Co, and Ni are abundant, and a large number of studies have found that their metal oxides, sulfides, nitride, phosphates, hydroxides and other derivatives can promote the OER process.…”
Section: Introductionmentioning
confidence: 99%
“…The overpotential of OER can be reduced and the energy conversion efficiency can be improved by using suitable electrocatalyst with high activity [15] . At present, Ru/Ir‐based and Pt‐based noble metal catalysts show excellent OER and HER electrocatalytic properties, but due to the scarcity and high production cost of such metals, they cannot be widely applied in commercial devices [16–18] . Thus, the exploitation of inexpensive and efficient non‐noble metal electrocatalysts has become a research priority [19–21] .…”
Section: Introductionmentioning
confidence: 99%
“…[ 34,35,42,71 ] However, the installation of variable functional groups on the outer polymer shell offers unprecedented opportunities for further (bio‐)chemical modification, including luminescence functionalization, and organelle and tissue targeting. [ 72–74 ] Filled hollow nanospheres, also referred to as yolk/shell NPs or nanorattles, open up new possibilities for functionalization so far out of reach with classical core/shell NPs for theranostic and quantitative MPI applications. [ 25,75–79 ] This superparamagnetic magnetite architecture made of phenolic resin hollow spheres coated with Eu(III) containing silica nanoparticles, herein named SMART RHESINs, was synthesized and studied.…”
Section: Introductionmentioning
confidence: 99%